CO-CURRENT DRYING IN HIGH-REVOLUTION ROTARY DRYER - Nascak, Dusan; Mikula, Jan; Kerekanic, Jan (European Scientific Journal, ESJ, 2014)
The high-revolution rotary dryer was developed for the biomass thermal treatment. The apparatus operates on the mechanical fluidization principles, which are achieved by the effect of centrifugal and gravitational forces. Centrifugal forces are growing by increasing the revolutions. With their influence, the fluidized material is uprising and by influence of gravitation forces is passing down to the lower part of the equipment. At critical revolutions, a balancing of centrifugal and gravitational forces is achieved. At this situation the fluidized material is filling the whole apparatus section. Thus, individual, longitudinal and transversal particular motion is achieved. At critical revolutions, the optimal conditions for heat transfer are created. Fluidized heat transfer surface is approaching to the whole surface of individual particles. Also because of radial and axial particular movement the heat transfer coefficient is growing and one order is higher as with classical dryers. High–revolution rotary dryer was used for biomass drying. Effective drying of this material enables its technological utilization. In this contribution characteristics of high-revolution rotary dryer are presented, the mathematical model was developed, simulation of drying process and proving on experimental device were implemented. The results prove adequacy of the proposed technology and their effective utilization.